Contemporary HRM Issues in the 21st century - Holland, Peter (Emerald Publishing Limited, 2019)
Contemporary HRM Issues in the 21st Century is an illuminating textbook for postgraduate students and active managers wanting to develop their understanding of issues and challenges emerging in the 21st century workplace from a HRM perspective. This edited collection, with contributions from experts in the field of HR policy development, is split into four sections. Section One explores the contemporary workforce and critical elements of managing HRM in a knowledge-based economy. Section Two focuses on psychological concerns for the individual at work, career management and emotional labour to better understand how to manage an increasingly diverse workforce. Section Three looks at managing HR issues in the workplace, such as crisis management, mental health and violence in the workplace. The final section of this book looks at current and emerging debates surrounding HRM, including: sustainable HRM; cyber-vetting; biological monitoring and surveillance; codes and conduct; job-design in the age of technology; and, Artificial Intelligence (AI). All of these are vital and often contentious areas within HRM policy-making and practice. This book sets out these debates and issues to engage both students and managers working in the fields of Global HRM and Human Resource policy-making.- Resumé vydavatel